Menilik Tantangan Pembangunan Kesehatan di Indonesia: Faktor Penyebab Stunting di Kabupaten Jember - Irma Fitriana Ulfah; Arief Budi Nugroho (Sospol : Jurnal Sosial Politik, 2020)
Abstract The prevalence of stunting of children under five in Indonesia is still high, namely 29.6% above the 20% limit set by WHO. In Jember Regency, the number of stunting sufferers reached 17,344 in 2018 and increased in 2019 to 19,870. Meanwhile, efforts to prevent stunting continue to be encouraged by both the central, regional, and village governments. The Local Government of Jember has promoted the 1000 HPK program, although the implementation is still facing obstacles. Thus, it is interesting to analyze the socio-economic factors that cause stunting and local government policies in handling stunting. The research method used is descriptive qualitative and purposive techniques to determine informants as sources. Meanwhile, data collection techniques consisted of in-depth interviews with open-ended questions, direct observation, and written documents. The results showed that the factors causing stunting were early marriage, low level of parental education, lack of income, and inadequate sanitation. Early marriage and low education lead to the unpreparedness of parents in raising children. Most of the informants work in the agricultural sector. In addition, some residents do not have access to proper drinking water and sanitation. The local government has released a good policy to abolished stunting in Jember. The local government also has a special program to improve public health which aims to reduce stunting rates. Bidan and Posyandu and their health committee play an important role in the effort to stunting reduction program. Some of the village governments in Jember have allocated funds to build health facilities such as Poskesdes.